Single-cell transcriptomic analysis reveals the commonality of immune response upon H1N1 influenza virus infection in mice and humans - Yu Chen; Huaiyuan Cai; Qian Zhang; Gang Cao; Jiahao Zhang; Bing Yang; Jinxia Dai (BMC, 2024)
Abstract Seasonal influenza A virus (IAV), particularly the H1N1 subtype, poses a significant public health threat because of its substantial morbidity and mortality rates worldwide. Understanding the immune response to H1N1 is crucial for developing effective treatments and vaccines. In this study, we deciphered the single-cell transcriptomic landscape of peripheral blood mononuclear cells (PBMCs) from H1N1-infected humans and lung tissue samples from H1N1-infected mice by mining HIN1-related single-cell RNA sequencing data from the GEO database. We observed similar changes in immune cell composition following H1N1 infection, with an increase in macrophages but a decrease in T cells in both species. Moreover, significant transcriptional changes in bystander immune cells upon H1N1 infection were identified, with the upregulation of the chemokine CCL2 in human PBMCs and increased expression of interferon-stimulated genes such as Ifit3, Ifit1 and Isg15 in mouse pulmonary immune cells. Intercellular cross-talk analysis highlighted enhanced interactions among bystander immune cells during H1N1 infection, with neutrophils in humans and macrophages in mice showing the most remarkable increases in interaction intensity. Transcription factor analysis revealed the conserved upregulation of key antiviral regulons, including STAT1 and IRF7, in T cells across both species, highlighting their pivotal roles in antiviral defense. These results suggest that humans and mice exhibit common immune responses to H1N1 infection, underscoring the similarity of vital immune mechanisms across species. The conserved immune mechanisms identified in this study provide potential therapeutic targets for enhancing antiviral immunity. Our research underscores the importance of understanding species-specific and conserved immune responses to H1N1 and offers insights that could inform the development of novel antiviral therapies and improve clinical outcomes for individuals affected by influenza.